RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN DENGAN DESAIN SISTEM BERORIENTASI OBJEK (STUDY KASUS : CV. ANGKUTAN AGUNG) - Nur Ali Farabi; Andi Rosano; Nur Annisa Tri Wulandari (Yayasan Akrab Pekanbaru, 2018)
Angkutan Agung is a company engaged in expedition, which employs many employees, the employee payroll system is still used manually by writing in a record book. This manual system will invite errors therefore there is a need for a solution that is used to overcome the accuracy in payroll because in order to avoid errors in recording or recapping salaries. Therefore, a computerized system is needed in order to provide information to employees and other parties appropriately, quickly and accurately, based on the description above, the writer is interested in making an object-oriented payroll information system on CV Angkutan Agung. This system is made using object-oriented methodology with UML tools (Unified Modeling language). The concept of data for ERD (entity relational diagram) and logical record structure (LRS) models. With the Java Netbeen.8.1 programming language and Mysql database. The results to be achieved from this study is that the employee salary calculation application can provide information in ease of presentation, improve performance and data processing to be better, more precise, fast, and accurate, and accelerate in making employee salary reports.